The Pitfall of Selective Environmental Information Disclosure on Stock Price Crash Risk: Evidence From Polluting Listed Companies in China - Xu, Fei; Ji, Qiang; Yang, Mian (Frontiers in Environmental Science, 2021)
Due to incomplete legal regulation, enterprises have the motive of selective environmental information disclosure (EID), and such selective disclosure strategy may result in stock price crash risk. In this study, the EID scores of China’s 1,010 polluting listed companies between 2007 and 2017 are first measured by employing the text analysis approach. Subsequently, we empirically examine the impacts of corporate’s selective EID on the stock price crash risk. The results indicate that EID of China’s polluting listed companies has significantly increased their stock price crash risk, rather than reducing it. Specifically, the EID of polluting companies with lower information efficiency, higher inefficient investment, higher degree of government control, and location in lower marketization areas is more likely to increase their stock price crash risk. Additional analyses reveal that the EID of polluting listed companies in China cannot reduce their stock price synchronization, which means that the selective disclosure of environmental information of China’s polluting listed companies is useless, and thus cannot reduce the risk of stock price crash.